PROFESSOR KOST’ KYSILEVS’KYI – THE RESEARCHER OF TARAS SHEVCHENKO’S LANGUAGE STYLE - Bihusiak, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses K. Kysilevs’kyi’s works devoted to the artistic language and scientific interpretation of Taras Shevchenko’s works, to the research of Shevchenko’s language style and spelling systems of the first three editions of “Kobzar’. The majority of the works were published in diaspora’s editions and were inaccessible for continental Ukraine.